PENGARUH BELANJA MODAL, TINGKAT SUKU BUNGA DAN INFLASI TERHADAP INVESTASI DI SULAWESI TENGGARA PERIODE 2001-2017 - Syamsir Nur; Manat Rahim; Nur Azisah (Universitas Halu Oleo, 2019)
This study aims to determine and analyze the effect of capital expenditure. Interest rates and inflation on investment in Southeast Sulawesi The data used in this study are investment data. Capital expenditure, interest rates and inflation in Southeast Sulawesi sourced from Bank Indonesia (BI) and the Central Statistics Agency (BPS). Using annual data from 2001-2017. This study uses multiple linear regression analysis. The software used is IBM SPSS Statistics 24. The results of this study indicate that simultaneously capital expenditure interest rates and inflation significantly influence investment in Southeast Sulawesi. Partially only the capital expenditure variable has a positive and significant effect on investment. Capital expenditure has a positive and significant effect on investment. Variable interest rates and inflation have no significant effect on investment in Southeast Sulawesi. The regional government of Southeast Sulawesi must always increase its capital expenditure allocation which has a direct impact on investment activities, as well as the condition of interest rates that must be kept in mind given the tendency of investors who invest in South East Sulawesi to also use loan capital sourced from the Province Southeast Sulawesi.